A Call for Computer Recess: The Impact of Computer Activities on Predominantly Minority Students' Technology and Application Self-Efficacy. (June 2020) - Ball, Christopher; Huang, Kuo-Ting; Francis, Jess; Kadylak, Travis; Cotten, Shelia R.
The digital divide limits the flow of potential students through the science, technology, engineering, and mathematics (STEM) pipeline and into STEM careers. The digital divide is a dynamic and constantly evolving concept of digital exclusion that encompasses numerous dimensions and levels. The "usage access gap" and the "second-level divide" both account for differences in how digitally divided people actually use technology. In this study, we employ social cognitive theory as a framework to explore the impact of various kinds of technology usage on predominately minority students' technology and application self-efficacy. Data were gathered over the course of a large-scale computing intervention that took place in an elementary school district in the southeastern United States. Results indicate that usage access gap activities and second-level divide activities, such as playing games or talking to friends online, may actually help increase students' technology self-efficacy and computer application self-efficacy. Entertainment and social networking activities provide students with positive direct experiences with technology, which may help close this dimension/level of the digital divide over time. Future computing interventions should consider establishing dedicated "computer recess" time to help digitally divided students increase their technology self-efficacy.